PENGARUH FINANCIAL STABILITY, KUALITAS AUDIT DAN KOMPLEKSITAS PERUSAHAAN TERHADAP FINANCIAL STATEMENT FRAUD - Krisanti, Maria Bambang; Nazar, Shinta Ningtiyas (Jurnal Nusa Akuntansi, 2025)
This study aims to find out and provide empirical evidence regarding the influence of financial stability, audit quality and company complexity on financial statement fraud in sector financials sub-sector banks listed on the Indonesia Stock Exchange in 2019-2023. The independent variables in this study are financial stability which is proxied by the asset change ratio (ACHANGE), audit quality measured by discretionary accruals proxies, and company complexity as measured by the number of subsidiaries. The dependent variable in this study is financial statement fraud as measured by the Beneish M-Score. This type of research is quantitative. This research uses secondary data in the form of annual financial statements from the Indonesia Stock Exchange (IDX). The population in this study is sector financials sub-sector banks listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique in this study used the purposive sampling method and was obtained from 15 companies with a span of 5 years, so that the data processed was as many as 75 data samples. The data analysis technique in this study uses the multiple linear analysis method and the data analysis tool in this study uses the Eviews 12 Student Version software program. The results of the study show that (1) financial stability has an effect on financial statement fraud, (2) audit quality has a significant negative effect on financial statement fraud, (3) company complexity has no effect on financial statement fraud, (4) financial stability, audit quality and company complexity simultaneously have a significant effect on financial statement fraud.